Perfil do leitor colonial - Araújo, Jorge de Souza (1988)
The profile of tendencies and characteristics of reading in colonial Brazil, emphasizing the interest provoked by works of prose and poetry in reading habits, constituted an imperative study in the area of Letters, with a view to preserving the national memory under the angle of literary culture. In an attempt to supply analysis and description elements of the colonial reader by means of the itemized list of books, included as goods in period inventories, since the seventeenth through the nineteenth century, this work is the result of research conducted all over the country to establish a safe register of options and stylistic tastes developed by the Brazilian reader, especially in what refers to literary works.